A differentiated approach to postoperative hormone-modulating therapy of patients with endometriosis - Kuzmina N.S; V.F. Bezhenar; Kuzmina N.S (LCC «Medicine-Inform», 2018)
A differentiated approach to postoperative hormone-modulating therapy of patients with endometriosis Kuzmina N.S.1,2, Bezhenar V.F.1, Kalugina A.S.1,2 1 Pavlov First Saint Petersburg State Medical University 2 AVA-PETER clinic, St.- Petersburg Aim: to compare the effectiveness of the use of various groups of medications for the treatment of infertility by the level of anti-Mullerian hormone (AMH), the number of follicles in the ovaries and the frequency of pregnancy. Patients and Methods: the study enrolled 172 patients with ovarian endometriomas who received hormone-modulating therapy after laparoscopic cystectomy: 82 patients received GNRH agonist - tryptorelin, 52 patients received gestagenes (dienogest), 21 patients received COCs and 17 patients did not receive hormone-modulating therapy and made up a control group. The levels of AMH, FSH in the blood serum, the number of follicles in the ovaries were determined in all patients before the start of the treatment and 6 months after the end of treatment. The frequency of pregnancy in all groups was estimated within 12 months after the treatment. Results: the least decrease in the level of AMH after treatment was observed in the group of patients receiving tryptorelin, a slightly larger difference was in the group of patients with dienogest, a more pronounced decrease of AMH in the COC group, and significantly more in the untreated group. In the group of patients who received tryptorelin, the level of AMH decreased less significantly among all 4 groups, on average from 3.95 to 2.08 ng / ml (p <;0.0001), the level of FSH increased from 6.0 to 7.88 IU / l (p <;0.0001), the number of follicles in the operated and intact ovaries decreased from 6.23 to 4.4 (p <;0.0001) and from 8.44 to 7.55 (p = 0.0000005), respectively. In patients of all the study groups pregnancy occurred in 27.4% of cases. In the group of patients receiving triptorelin, pregnancy occurred in 36%, dienogest - 32.5%, COC - 5.26%, in the group of patients who did not receive treatment, the pregnancy occurred in 5.9%. Conclusion: GNRH-agonist drugs and progestins are the most effective groups of drugs for the complex treatment of endometriosis in patients with infertility, while COC, according to the study, can not be a drug of choice for the purpose of hormone-modulating therapy in the treatment of infertility. Key words: infertility, ART, IVF, tryptorelin, dienogest, combined oral contraceptives, anti-Mullerian hormone. For citation: Kuzmina N.S., Bezhenar V.F., Kalugina A.S. A differentiated approach to postoperative hormone-modulating therapy of patients with endometriosis // RMJ. 2018. № 2(I). P. 65-69.